2011
DOI: 10.1111/j.1743-7563.2011.01391.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in medical oncology admissions for the management of breast cancer complications: An Australian institution's experience

Abstract: Although total annual breast cancer admission numbers and length of stay did not change significantly, hospitalization for treatment-related complications was less frequent in 2006. The clinical manifestations of metastatic breast cancer appear to be changing, and in our institution are being managed with broader multidisciplinary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Another study described 83 patients with MBC who were admitted to a medical oncology inpatient unit in Australia and demonstrated that only approximately 15% of admissions in 2006 received a palliative care consult. 25 Our study confirms the low rates of palliative care and hospice utilization in this population. By focusing on patients hospitalized for the first time with MBC, we have identified a distinct event in these patients’ course of illness for clinicians to consider which patients may benefit from palliative care and hospice services.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Another study described 83 patients with MBC who were admitted to a medical oncology inpatient unit in Australia and demonstrated that only approximately 15% of admissions in 2006 received a palliative care consult. 25 Our study confirms the low rates of palliative care and hospice utilization in this population. By focusing on patients hospitalized for the first time with MBC, we have identified a distinct event in these patients’ course of illness for clinicians to consider which patients may benefit from palliative care and hospice services.…”
Section: Discussionsupporting
confidence: 83%
“…Despite the high symptom burden and poor prognosis of patients in this study, palliative care was consulted in only 6.8% of admissions, and 18% of patients enrolled in hospice upon discharge. Another study described 83 patients with MBC who were admitted to a medical oncology inpatient unit in Australia and demonstrated that only approximately 15% of admissions in 2006 received a palliative care consult (25). Our study confirms the low rates of palliative care and hospice utilization in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients presenting with non‐neutropenic fever were managed as outpatients (82%), while nearly all presentations with neutropenic fever resulted in hospital admission (93%). Due to the potential sequelae of life‐threatening sepsis, neutropenic fever is the ED presentation reason most likely to result in hospital admission, both in early breast cancer patients and the broader cancer population . Neutropenic fever accounted for a higher proportion of ED presentations in our study (24%) than in early breast cancer patients in Canada (9%) .…”
Section: Discussionmentioning
confidence: 65%
“…Rates of admission to hospital with serious complications have mostly been reported to be in the range 20% to 25% [5][6][7] and there is a small risk of early death from treatment, reported to be in the range 0.2% to 0.3% in recent studies. 8,9 Patients are frequently unable to work both during treatment and for some time thereafter, 10 which has considerable cost to society.…”
Section: Chapter 1 Backgroundmentioning
confidence: 99%